2019
DOI: 10.1002/mma.5641
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical study of fractional order differential equations of predator‐pest models

Abstract: To explore the impact of pest‐control strategy through a fractional derivative, we consider three predator‐prey systems by simple modification of Rosenzweig‐MacArthur model. First, we consider fractional‐order Rosenzweig‐MacArthur model. Allee threshold phenomena into pest population is considered for the second case. Finally, we consider additional food to the predator and harvesting in prey population. The main objective of the present investigation is to observe which model is most suitable for the pest con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…On the other hand, since fractional-order differential operators can fit the memory and heritability of population growth well, making the models established by fractional-order derivatives more accurate than integer-order models, scholars began to use fractional-order differential equations to explore the dynamics of population ecosystems and broaden the applicability of population models. Mandal et al [40] introduced the fractional-order Rosenzweig-MacArthur model to explore pest control strategies and found that the proposed fractional-order model is more stable and more suitable for pest management than the corresponding integer-order model. Yousef et al [41] established a fractional-order predator-prey system with fear effect, studied the effects of fear effect on the reproduction rate and mortality rate of the prey population, and found that the fractional derivative can stabilize the proposed system due to the memory effect.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, since fractional-order differential operators can fit the memory and heritability of population growth well, making the models established by fractional-order derivatives more accurate than integer-order models, scholars began to use fractional-order differential equations to explore the dynamics of population ecosystems and broaden the applicability of population models. Mandal et al [40] introduced the fractional-order Rosenzweig-MacArthur model to explore pest control strategies and found that the proposed fractional-order model is more stable and more suitable for pest management than the corresponding integer-order model. Yousef et al [41] established a fractional-order predator-prey system with fear effect, studied the effects of fear effect on the reproduction rate and mortality rate of the prey population, and found that the fractional derivative can stabilize the proposed system due to the memory effect.…”
Section: Introductionmentioning
confidence: 99%